2021
DOI: 10.1093/nsr/nwab187
|View full text |Cite
|
Sign up to set email alerts
|

Probing the internal structure of baryons

Abstract: Electromagnetic form factors are fundamental observables that describe the electric and magnetic structure of hadrons and provide keys to understand the strong interaction. At the Beijing Spectrometer (BESIII), form factors have been measured for different baryons in the time-like region for the first time or with the best precision. The results are presented with examples focus on but not limited to the proton/neutron, the Λ, with a strange quark, and the Λc, with a charm quark.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Within this paper, only former results, as well as future experiments employing the scan method, are reviewed, whereas an overview of results with the ISR method can be found in [15]. Further reviews about nucleon EM FFs in the TL region in general and other baryon FFs can be found in [16] and [17], respectively.…”
Section: Scan Methodsmentioning
confidence: 99%
“…Within this paper, only former results, as well as future experiments employing the scan method, are reviewed, whereas an overview of results with the ISR method can be found in [15]. Further reviews about nucleon EM FFs in the TL region in general and other baryon FFs can be found in [16] and [17], respectively.…”
Section: Scan Methodsmentioning
confidence: 99%
“…There are rich physics outputs from Λ Λ studies at BESIII [13,14,[21][22][23][24]. Besides, BESIII has measured the production cross sections of various baryon pairs in the time-like region [25]. Despite the fact that there are wide physics programs at BESIII concerning the production of Λ Λ at ψ [22] resonances, and the polarization of Λ at different c.m.…”
Section: The Besiii At Bepciimentioning
confidence: 99%
“…Electromagnetic form factors (EMFFs) parameterizing the inner structure and dynamics of hadrons are fundamental observables of nucleons and hyperons to understand the QCD effects in hadronic resonances [1][2][3][4][5][6]. In the 1960s, Cabibbo et al [7] first proposed that time-like EMFFs can be studied on e + e − collider experiments by measuring the hadron pair production cross sections, such as the exclusive hyperon cross section.…”
Section: Introductionmentioning
confidence: 99%